Evaluation of bacteria isolated from the gastrointestinal tract of termites (Coptotermes curvignathus) as potential probiotics - Abu Hassan, Siti Aminah; King, Patricia Jie Hung; Sarbini, Shahrul Razid (Scientific Array, 2019)
Exploration of new environment provide an opportunity for better probiotics to be applied as valuable functional food. One interesting ecosystem is the gut of termites, where it contains bacterial populations to assist the host in extracting energy from polysaccharides of heavy fibre diet. This study screen, isolate and identify potential probiotic microorganisms from the hindgut of termites particularly from the species Coptotermes curvignathus. Bacterial isolates from the gut of Coptotermes curvignathus were tested for their potential as probiotics, with special reference to resistance to low pH, and tolerance to bile. The preliminary result showed that ten isolates can survive in low pH and five can survive in bile concentration. The five isolates were further tested on high concentrations of bile, antibiotic resistance and antimicrobial activity against pathogen i.e. Escherichia coli, Salmonella typhi, Shigella dysenteriae, Staphylococcus aureus, Vibrio cholera and Enterococcus faecalis tested by well diffusion method. For antibiotic resistance analysis, erythromycin, gentamycin, cefotaxime, meropenem, chloramphenicol, tetracycline, ciprofloxacin, and ampicillin were included by the disc-diffusion method. The isolate ATP022 had thrived well in low pH condition. The isolate ATP023 showed good capability in antibiotic resistance evaluation. The isolate ATP028 grows well in stimulated gastrointestinal juice. Moreover, the isolate ATP028 showed good result in tolerance in high concentration of bile. However, all isolates including the established probiotics i.e. Lactobacillus rhamnosus, did not perform well in the antimicrobial activity against pathogens. All five bacterial isolates were revealed from the genus Citrobacter. In conclusion, the ATP028 and ATP023, isolated form the gut of termite Coptotermes curvignathus have the best potential as probiotic with high tolerance to stimulated gastrointestinal juice, bile salts and antibiotic test.